2019
DOI: 10.3390/cells8040290
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Non-Structural Protein 5A (NS5A) Disrupts Mitochondrial Dynamics and Induces Mitophagy

Abstract: Mitophagy is a selective form of autophagy, targeting damaged mitochondria for lysosomal degradation. Although HCV infection has been shown to induce mitophagy, the precise underlying mechanism and the effector protein responsible remain unclear. Herein, we demonstrated that the HCV non-structural protein 5A (NS5A) plays a key role in regulating cellular mitophagy. Specifically, the expression of HCV NS5A in the hepatoma cells triggered hallmarks of mitophagy including mitochondrial fragmentation, loss of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…The tight interactions between ROS accumulation and microglial overactivation and autophagy are mainly reflected in two ways: the induction of autophagy by ROS accumulation or microglial overactivation [49][50][51] and the reduction of ROS accumulation or microglial overactivation via autophagy [52,53], which is complex, and depends on the region, severity and phase of the insult. In our present study, CCH might impair the processes of autophagy and mitophagy through upregulation of ROS generation and microglial overactivation, indicating that neuroinflammation may play a more dominant role than impaired autophagy at the stage of chronic cerebral ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…The tight interactions between ROS accumulation and microglial overactivation and autophagy are mainly reflected in two ways: the induction of autophagy by ROS accumulation or microglial overactivation [49][50][51] and the reduction of ROS accumulation or microglial overactivation via autophagy [52,53], which is complex, and depends on the region, severity and phase of the insult. In our present study, CCH might impair the processes of autophagy and mitophagy through upregulation of ROS generation and microglial overactivation, indicating that neuroinflammation may play a more dominant role than impaired autophagy at the stage of chronic cerebral ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…HCVinduced mitophagy correlates with deregulation of oxidative phosphorylation and depletion of mitochondria, which could contribute to liver injury (Kim et al, 2013a). Recently, it has been reported that the overexpression of NS5A is sufficient to induce Parkin translocation to the mitochondria and, consequently, mitophagy in a ROS-dependent manner (Jassey et al, 2019), while Core protein was demonstrated to inhibit mitophagy by inhibiting Parkin translocation to the mitochondria (Hara et al, 2014). A possible explanation to reconcile these conflicting evidences could be that, as well as bulk autophagy, HCV may also temporally regulate mitophagy depending on the expression level of NS5A and Core.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…The human hepatoma Huh-7 cells were cultured in DMEM containing 10% FBS, 1% gentamycin, 1% amphotericin B, and incubated at 37 • C in a 5% CO 2 incubator. The AB12-A2 Huh-7 replicon cells carrying the HCV genotype 1b subgenomic RNA (denoted as 'Huh-7.HCVrep') were similarly maintained in DMEM, but supplemented with 1 mg/mL of G418 (InvivoGen; San Diego, CA, USA), as previously described [46]. Huh-7 cells persistently producing infectious cell culture-derived HCV particles (denoted as 'Huh-7.HCVcc') were initially established by electroporation of the full-length HCV genome Jc1FLAG2 (p7-nsGluc2A), as previously described [47], and then continuously passaged in media containing HCVcc particles until all cells tested positive for HCV NS5A expression.…”
Section: Cell Culturementioning
confidence: 99%